959. HIV-1 DNA Testing Identifies Drug Resistance in Viremic Patients with Pan-Sensitive Plasma Virus. (31st December 2020) - Curanovic, Dusica; Martens, Sharon K; Rodriguez, Milka A; Hammill, Hunter A; Petropoulos, Christos J; Walworth, Charles M
Abstract: Background: HIV-1 drug resistance mutations (DRMs) are lost from plasma virus in the absence of selective drug pressure. Therefore, viremic patients who present with pan-sensitive plasma HIV-1 may harbor archived drug resistance that hinders virologic suppression upon reinstatement of therapy. We sought to determine if testing HIV-1 DNA in peripheral blood mononuclear cells (PBMCs) can identify drug resistance in patients with pan-sensitive plasma virus. Methods: Sixty-four patients were identified who had HIV-1 RNA and HIV-1 DNA drug resistance testing performed on the same day and demonstrated pan-sensitive virus on the HIV-1 RNA test. Antiretroviral (ARV) resistance and DRMs identified by each test were compared between 66 test pairs. Patients were stratified by viral load (VL) to assess its impact on resistance detection using t-test and correlation analyses. Results: The mean patient age was 37; 92% were female. Most (94%) were infected with HIV-1 subtype B, with an average VL of 110, 000 c/mL (150 - 1, 470, 000 c/mL) at the time of resistance testing. Resistance to at least one ARV was reported on 20% (13/66) of HIV-1 DNA tests, and was associated with nucleos(t)ide and non-nucleoside reverse transcriptase inhibitors (NRTIs and NNRTIs), protease inhibitors (PIs), and integrase inhibitors (INIs) on 4.5%, 9%, 4.5%, and 6% of HIV-1 DNA reports, respectively. Across all HIV-1 DNA tests, 74 DRMs were identified that were not found in the plasma virus, including 12 NRTI, 16 NNRTI, 39 PI, and 7 INI DRMs; M184V was identified on 4.5% (3/66) of HIV-1 DNA reports. The mean VL was not significantly different between HIV-1 DNA tests reporting resistance to at least one ARV (101, 000 c/mL) and those reporting pan-sensitivity (110, 000 c/mL). Viral load at time of testing did not correlate with the number of ARVs to which resistance was reported. Conclusion: In viremic patients with pan-sensitive plasma virus, HIV-1 DNA testing can identify drug resistance regardless of VL level. Assessment of drug resistance in HIV-1 DNA may be useful in designing suppressive ARV regimens for patients whose plasma virus DRMs fail to be identified due to lack of adherence or continuity of care. Disclosures: Dusica Curanovic, PhD, Monogram Biosciences (Employee) Sharon K. Martens, MN, Monogram Biosciences (Employee) Milka A. Rodriguez, PhD, Monogram Biosciences (Employee) Christos J. Petropoulos, PhD, Monogram Biosciences (Employee) Charles M. Walworth, MD, Monogram Biosciences (Employee)